PENERAPAN FACE RECOGNITION DENGAN ALGORITMA VIOLA JONES DALAM SISTEM PRESENSI KEHADIRAN SISWA DAN GURU PADA SEKOLAH IDN BOARDING SCHOOL JONGGOL - Mulyana, Dadang Iskandar; Edi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The Viola-Jones algorithm is one algorithm that is often used to detect faces. The human face recognition system is an important technology that functions as a security system, control system, and others. This is in accordance with the research objectives, namely to determine the application of the Viola-Jones algorithm in detecting the faces of students and teachers at SMK IDN Boarding School. This research aims to develop a student and teacher attendance system at IDN Boarding School Jonggol using face recognition technology with the Viola-Jones algorithm. The developed attendance system aims to increase the effectiveness and efficiency in managing the attendance of students and teachers. Then identify attendance by comparing face images registered in the system database. The application used by the face recognition program is PyCharm Community 2023 Version 1.4 with the macOS operating system. The test used various expressions totaling 200 images of 20 people. The percentage of successful face recognition process is 95%. Some factors that affect the success of recognition are lighting, face distance and face position.